2017
DOI: 10.1016/j.jcrysgro.2017.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and control of ZnGeN2 cation lattice ordering

Abstract: ZnGeN2 and other heterovalent ternary semiconductors have important potential applications in optoelectronics, but ordering of the cation sublattice, which can affect the band gap, lattice parameters, and phonons, is not yet well understood. Here the effects of growth and processing conditions on the ordering of the ZnGeN2 cation sublattice were investigated using x-ray diffraction and Raman spectroscopy. Polycrystalline ZnGeN2 was grown by exposing solid Ge to Zn and NH3 vapors at temperatures between 758 deg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 37 publications
(54 reference statements)
3
46
0
Order By: Relevance
“…Another recent review is by Martinez et al Our group has also created a website dedicated to these materials at https://sites.google.com/a/case.edu/dmref/home. Until recently the most studied of these materials was ZnGeN 2 , the closest analog of GaN . Since 2012, ZnSnN 2 has also received significant attention as a potential solar cell material based on sustainable elements .…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Another recent review is by Martinez et al Our group has also created a website dedicated to these materials at https://sites.google.com/a/case.edu/dmref/home. Until recently the most studied of these materials was ZnGeN 2 , the closest analog of GaN . Since 2012, ZnSnN 2 has also received significant attention as a potential solar cell material based on sustainable elements .…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, experimentally, it was found that ZnGeN 2 can occur either in a disordered or ordered form (based on XRD and Raman spectra) depending on the growth temperature, with the disordered form occurring at lower temperature. This indicates the disorder is not a thermodynamic disorder but kinetically controlled by the lower surface mobility of atoms during growth at low temperature.…”
Section: Disorder and The Octet Rulementioning
confidence: 99%
See 2 more Smart Citations
“…Further to replacing scarce elements, the replacement of one atom type by a combination of two others adds a degree of structural complexity to the structure that can greatly influence the electronic properties. It has, for instance, been demonstrated that cation order/disorder phenomena in Zn B N 2 ( B = Sn, Ge) can reach from fully disordered structures in the wurtzite‐type to fully ordered ones in the β ‐NaFeO 2 ‐structure type and that the order–disorder transition causes a drastic band gap change . However, zinc germanium oxide nitrides (ZGON) have been reported to adopt the wurtzite‐type structure as well, and can hence mimic similar effects.…”
Section: Introductionmentioning
confidence: 99%